Perspective in Pediatric Pathology, Chapter 24. Testicular Inflammatory Processes in Pediatric Patients - Nistal, Manuel; Paniagua, Ricardo; González-Peramato, Pilar; Reyes-Múgica, Miguel (Pediatric and developmental pathology, 2016)
Acute scrotal pain in children represents a major diagnostic and therapeutic challenge. An important initial differentiation should be made between epididymitis and other processes that cause acute scrotal pain, such as testicular torsion and tumor. Infectious agents disseminating through the blood flow can damage the testis by causing orchitis. On the other hand, infections ascending via spermatic pathways typically lead to epididymitis [1].